Quality of periodic health examination service for employees and associated factors at the New Port Medical Center, Ho Chi Minh city in 2020 - Pham Thi, Thuy; Nguyen Duc, Thanh; Dau Quoc, Tran; Tran Nhu, Thao (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objectives: A periodic health examination helps people to evaluate the overall health status, so it is of the utmost importance to each individual, including employees. At Saigon Newport Corporation, employees have to do strenuous, hazardous, and dangerous works, so periodic health examination is necessary.Methods: A descriptive cross-sectional study was conducted on 436 employees to measure their perception of the periodic health examination service quality via the SERVPERF scale and associated factors at the New Port Medical Center, Ho Chi Minh City, 2020.Results: Research results indicated that 78% of employees have a good assessment of the quality of periodic health examination, in which reliability was 79.6%, assurance was 79.8%, which were also the least.Conclusions: Gender, level of education, and sector of employment were related to the employees’ perception of the periodic health examination service.
Keywords: Periodic health examination; employee; SERVPERF; New Port Medical Center; Saigon Newport Corporation.